2005
DOI: 10.1007/s11107-005-2484-2
|View full text |Cite
|
Sign up to set email alerts
|

Multihop Virtual Topology Design in WDM Optical Networks for Self-Similar Traffic

Abstract: Abstract. In this paper, we consider the problem of designing virtual topologies for multihop optical WDM networks when the traffic is self-similar in nature. Studies over the last few years suggest that the network traffic is bursty and can be much better modeled using self similar process instead of Poisson process. We examine buffer sizes of a network and observe that, even with reasonably low buffer overflow probability, the maximum buffer size requirement for self-similar traffic can be very large. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 32 publications
(48 reference statements)
0
23
0
Order By: Relevance
“…In order to evaluate the performance of the different versions of GALD, a simulation study was developed in a simulator based on OMNeT++ using the 14-node NSFNet (Ghose et al, 2005) as network topology and assuming that cables consisted of two unidirectional fibers (one for each direction). The capacity of a wavelength was set to 10 Gbps and the traffic load was normalized by the lightpath capacity.…”
Section: Results Obtained With the Methodsmentioning
confidence: 99%
“…In order to evaluate the performance of the different versions of GALD, a simulation study was developed in a simulator based on OMNeT++ using the 14-node NSFNet (Ghose et al, 2005) as network topology and assuming that cables consisted of two unidirectional fibers (one for each direction). The capacity of a wavelength was set to 10 Gbps and the traffic load was normalized by the lightpath capacity.…”
Section: Results Obtained With the Methodsmentioning
confidence: 99%
“…Although, Poisson process has been vastly used in the past to model traffic in conventional networks, recently it has been shown that Internet traffic exhibits selfsimilar bursts [12,24]. We provide a mathematical formulation for the two traffic models below.…”
Section: Average Delaymentioning
confidence: 99%
“…Such a topology design should consider simultaneous optimization of network cost, average delay, and number of packets delivered subject to reliability, bandwidth and/or flow-constraints. Moreover as shown in [12,24] , the traffic model considered should be self similar in nature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of heuristic algorithms are given in the literature [Banerjee et al, 2000;Ozdaglar et al, 2003]. [7]Ghose, Kumar, Banerjee and Dutta [Ghose et al, 2005] compared the queuing delay in an optical network using both Poisson and self-similar traffic. They showed that the virtual topologies designed using self-similar traffic are more effective in handling present day brusty Internet traffic.…”
mentioning
confidence: 99%